1990
DOI: 10.1093/jnci/82.4.310
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of the Retinoblastoma Gene in Human Colorectal Carcinomas Relative to Normal Colonic Mucosa

Abstract: We report the first evidence of increased levels of the retinoblastoma (Rb) message in a majority of colorectal cancers when compared with normal mucosa. Southern blot analysis showed an increase in Rb gene copy number in at least 28% of colorectal carcinomas relative to normal mucosa. These results plus previous reports of nonrandom chromosome 13 gains in approximately 50% of colorectal cancers suggest that an increase in Rb gene copy number occurs frequently in these tumors. Possible mechanisms pertaining to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
40
0
2

Year Published

1991
1991
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 0 publications
9
40
0
2
Order By: Relevance
“…There were significantly more tumours with heterozygous loss on chromosome Ip than within the Rb locus (X2 = 6.7, P<0.01), and there tended to be more tumours with heter- Fearon & Vogelstein, 1990 The retinoblastoma gene acts as a tumour suppressor gene, and is known to be involved in several human malignancies (for reviews, see Benedict et al, 1990;Marshall, 1991). In a cytogenetic study on colorectal carcinomas, a non-random gain of chromosome 13 has been demonstrated (Muleris et al, 1988), and in a smaller colorectal carcinoma study, a significant amplification of the Rb gene was demonstrated both at the DNA and RNA levels (Gope et al, 1990), both studies suggesting that the Rb gene may be involved in colorectal carcinogenesis. The findings of the latter report have recently been confirmed by Lothe et al (1991).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…There were significantly more tumours with heterozygous loss on chromosome Ip than within the Rb locus (X2 = 6.7, P<0.01), and there tended to be more tumours with heter- Fearon & Vogelstein, 1990 The retinoblastoma gene acts as a tumour suppressor gene, and is known to be involved in several human malignancies (for reviews, see Benedict et al, 1990;Marshall, 1991). In a cytogenetic study on colorectal carcinomas, a non-random gain of chromosome 13 has been demonstrated (Muleris et al, 1988), and in a smaller colorectal carcinoma study, a significant amplification of the Rb gene was demonstrated both at the DNA and RNA levels (Gope et al, 1990), both studies suggesting that the Rb gene may be involved in colorectal carcinogenesis. The findings of the latter report have recently been confirmed by Lothe et al (1991).…”
Section: Resultsmentioning
confidence: 98%
“…The Rb gene has been shown to suppress tumour development (Bookstein et al, 1990), and the gene is therefore classified as a tumour suppressor gene. Little is known about the involvement of this gene in colorectal tumourigenesis. However, in a small series of colorectal carcinomas, it has recently been reported a significant amplification of the Rb gene (Gope et al, 1990).…”
mentioning
confidence: 97%
“…A major difference between the colon and other tissues is the notable lack of RB-1 deletion or mutation in colorectal cancer (Meling et al, 1991;Ali et al, 1993) indicating that the inactivation of RB-1 is not required for the development of colorectal tumorigenesis. In addition, the rise in the level of RB-1 mRNA in colonic tumours compared to that in normal colonic mucosa (Gope et al, 1990), together with the associated increase in pRb phosphorylation (Gope and Gope, 1992) suggest that the active Rb protein is retained and indeed up-regulated in colonic tumorigenesis. This is further supported by the fact that Rb protein associated with elevated levels of transcripts appears to be normal size (4.7 kb) and functional (Ali et al, 1993), inferring that colorectal cancer cells retain functional pRb.…”
Section: Discussionmentioning
confidence: 99%
“…However, loss or inactivation of the RB-1 gene in colorectal tumours is uncommon (Meling et al, 1991;Ali et al, 1993); only up to 11% of colorectal carcinomas show allelic loss on chromosome 13 (Wildrick and Bowman, 1994). Instead, colorectal tumours have been reported to express significantly higher levels of RB-1 mRNA than normal colonic mucosa (Gope et al, 1990). This increase coincides with a 1.5-2.5 fold increase in percentage of pRb phosphorylation (Gope and Gope, 1992), which is thought to be due to over-expression of the Rb-related kinases cdk2 and cdc2 (Yamamoto et al, 1995).…”
mentioning
confidence: 95%
“…12,14 At the genomic level, allelic loss detected by loss of heterozygosity (LOH) has also been reported in the RB1 region in CRC with widely differing frequencies ranging from 11.5% 15 to as high as 50% of cases studied.…”
mentioning
confidence: 99%